2021
DOI: 10.3390/antibiotics10040380
|View full text |Cite
|
Sign up to set email alerts
|

Trueperella pyogenes Isolates from Livestock and European Bison (Bison bonasus) as a Reservoir of Tetracycline Resistance Determinants

Abstract: Determinants of tetracycline resistance in Trueperella pyogenes are still poorly known. In this study, resistance to tetracycline was investigated in 114 T. pyogenes isolates from livestock and European bison. Tetracycline minimum inhibitory concentration (MIC) was evaluated by a microdilution method, and tetracycline resistance genes were detected by PCR. To determine variants of tetW and their linkage with mobile elements, sequencing analysis was performed. Among the studied isolates, 43.0% were tetracycline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 71 publications
(55 reference statements)
0
12
0
3
Order By: Relevance
“…These findings are consistent with the results reported in other studies regarding AMR of LAB ( 31 , 40 42 , 60 ). The simple explanation could be a mutation and mismatches at the primer annealing site that prevents detection of the target resistance gene ( 68 ). The phenotype-genotype discrepancies observed in our study could be also explained by the fact that other resistance genes may exist that were not investigated by us; however the number of the known resistance genes continues to increase.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the results reported in other studies regarding AMR of LAB ( 31 , 40 42 , 60 ). The simple explanation could be a mutation and mismatches at the primer annealing site that prevents detection of the target resistance gene ( 68 ). The phenotype-genotype discrepancies observed in our study could be also explained by the fact that other resistance genes may exist that were not investigated by us; however the number of the known resistance genes continues to increase.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, due to the frequent isolation of T. pyogenes from lesions in European bison, the antimicrobial resistance of the obtained isolates is also worth consideration. Despite the fact that European bison are less exposed to the antibiotic pressure, it should be mentioned that our previous studies showed the resistance to tetracycline and kanamycin among T. pyogenes strains isolated from these animals [ 40 , 41 ]. Therefore, T. pyogenes occurring in European bison may be a potential reservoir of resistance determinants, including the tetracycline resistance genes detected previously [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The studied strains were isolated from individual animals from different farms, with the exception of nine strains originating from three goats (strains 28/K, 30/K, 31/K, 34/K, strains 26/K, 27/K and strains 21/K, 22/K, 54/K were isolated from the goat 3, the goat 2 and the goat 1, respectively). All strains were identified using the API Coryne test (BioMérieux, Marcy l’Etoile, France) and also by the species-specific plo gene PCR, as described previously [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%